2011
DOI: 10.1002/clc.20942
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Torsional Mechanics in Uncomplicated Pregnancy

Abstract: Background: Alterations in left ventricular (LV) twist (torsion) and untwist have been described for a variety of physiologic and pathologic conditions. Little information is available regarding changes in these parameters during normal pregnancy. Hypothesis: Pregnancy is associated with significant changes in LV torsional mechanics. Methods: Left ventricular twist and untwist was measured in 32 pregnant females (mean gestation 199 ± 48 d) and 23 nonpregnant controls using speckle-tracking echocardiography.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…Recently, using this echocardiographic technique, a small decrease in LV segmental longitudinal systolic and diastolic function, as well as changes in torsion and peak LV twist velocity, in hearts of women with otherwise normal pregnancies were reported . Thus, in the current study we employed indexes derived from both TDI and speckle tracking techniques, in addition to the more traditional methods, to study cardiac function in a unique group of patients to whom these methods have not yet been applied: those with significant SOB with no other known systemic or obstetric problem and no obvious reason on clinical investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using this echocardiographic technique, a small decrease in LV segmental longitudinal systolic and diastolic function, as well as changes in torsion and peak LV twist velocity, in hearts of women with otherwise normal pregnancies were reported . Thus, in the current study we employed indexes derived from both TDI and speckle tracking techniques, in addition to the more traditional methods, to study cardiac function in a unique group of patients to whom these methods have not yet been applied: those with significant SOB with no other known systemic or obstetric problem and no obvious reason on clinical investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Yoon et al 12 reported significant changes in torsion and peak LV twist velocity in the 2nd and 3rd trimester compared with nonpregnant controls, while another study by Tzemos et al 11 found that torsion increased significantly during pregnancy in women with a bicuspid aortic valve and valve stenosis, as well as in pregnant women without valve pathology, compared with nonpregnant controls. Moreover, values of twist and peak systolic twisting rate in the 3rd trimester were significantly greater than in control subjects.…”
Section: Left Ventricular Twist During Pregnancymentioning
confidence: 97%
“…12 Peak untwisting rate has been described as a more sensitive, load-independent marker of diastolic function as it largely occurs during isovolumic relaxation time. To our knowledge, this is the first time that an enhanced peak untwisting rate during pregnancy has been described.…”
Section: Untwisting Rate During Pregnancymentioning
confidence: 99%
See 2 more Smart Citations